Analysis of Perceptions of Farmers toward the Efforts to Develop the Dual Role of Subak in an Upcoming Tourism Destination in Jatiluwih, Bali - USTRIYANA, I Nyoman Gede; BUDIASA, I Wayan; LIES ANGGRENI, I Gusti Agung (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
The establishment of an agricultural cooperative ( koperasi tani ) is an effort to empower subak , a traditional organization for water utilization and/or crop management for famers in Bali. The outcome expected is that for this institution to be able to play a double role: a traditional irrigation management institution as well as an integrated agribusiness-tourism management agency. The purpose of this study is to examine the perception of farmers toward the possibility to develop agricultural cooperatives through subak in an upcoming tourism destination. This study was carried out in Subak Jatiluwih in Bali, Indonesia, which has been designated by the UNESCO as one of the sites that became the World Cultural Heritage. Data were collected through interviews with 70 farmers using a structured questionnaire that was tested previously and through focus group discussion (FGD) during the period of June to August 2018. Perceptions of farmers were reviewed from indicators of knowledge and attitudes and measured using each of the 20 statements using a Likert scale. Data were then analyzed using descriptive statistics. The results show that perceptions of farmers toward the possibility of developing agricultural cooperatives through subak are within good category. When farmers have good perception, it is expected that the process of developing agricultural cooperatives through subak can be realized quickly and synergized with tourism businesses.